2014
DOI: 10.1260/1369-4332.17.10.1403
|View full text |Cite
|
Sign up to set email alerts
|

Statically-Indeterminate SFRC Columns under Cyclic Loads

Abstract: The present study is aimed at examining the structural response of steel-fibre-reinforced concrete (SFRC) columns under reversed-cyclic loading, which were investigated by means of non-linear finite-element analysis (NLFEA). The focus was on investigating the potential of steel fibres in compensating for reduction in conventional transverse reinforcement [and thus the spacing between shear links was increased by 50% and 100% while the fibre volume fraction ( V f) was increased to 1%, 1.5%, 2% and 2.5%]. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The statically-indeterminate arrangement also allows for a study of the effect of fibres on strength, ductility as well as moment redistribution and formation of plastic hinges. The discussion presented herein is limited to the validation of the FE model against the experimental data, whilst the findings from an FE-based full parametric study carried out on these columns under both types of lateral loading can be found elsewhere [18,19]. For FE modelling purposes, the lateral load (whether monotonic or cyclic) was applied using a displacement-based method at point C in Fig.…”
Section: Statically-indeterminate Sfrc Columns Subjected To Combined mentioning
confidence: 99%
See 1 more Smart Citation
“…The statically-indeterminate arrangement also allows for a study of the effect of fibres on strength, ductility as well as moment redistribution and formation of plastic hinges. The discussion presented herein is limited to the validation of the FE model against the experimental data, whilst the findings from an FE-based full parametric study carried out on these columns under both types of lateral loading can be found elsewhere [18,19]. For FE modelling purposes, the lateral load (whether monotonic or cyclic) was applied using a displacement-based method at point C in Fig.…”
Section: Statically-indeterminate Sfrc Columns Subjected To Combined mentioning
confidence: 99%
“…The structural configurations considered herein include a wide range of SFRC specimens ranging from simply-supported SFRC beams with no conventional reinforcement to more complex (statically indeterminate, consisting of more than one structural elements and subjected to a combination of axial and lateral loading) SFRC structural configurations fully reinforced. It should be pointed out that although some of the case studies are presented herein for the first time, others have formed the basis for parametric investigations carried out recently assessing the effect of the fibre-content on RC structural responses [14][15][16][17][18][19][20]. The reason for presenting all the cases in the present article is to show the objectivity of the numerical model employed.…”
Section: Introductionmentioning
confidence: 99%
“…The work is based on dynamic Nonlinear Finite Element Analysis (NLFEA), which was initially validated using exiting experimental data to ascertain its accuracy before the subsequent parametric studies were carried out. The work builds on previous NLFEA-based studies on various SFRC structural configurations subjected to both static monotonic and cyclic loading (the specimens covered a wide practical range from simply-supported beams to more complex structural systems characterised by a certain degree of static indeterminacy, such as continuous columns and beamcolumn sub-assemblages) [8][9][10][11]. Both previous and current studies utilize a material model for SFRC that is focused on realistically describing the fully brittle tensile behaviour of plain concrete as well as the contribution of steel fibres to the post-cracking response.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of steel fibres into the concrete mix can also lead to a reduction of transverse (i.e. shear) reinforcement such as beams, walls, joint regions [8][9][10][11]15] without compromising design codes [16,17] performance requirements for strength and ductility. The main benefit of such reduction is to alleviate reinforcement congestion due to dense arrangement and spacing of shear links in the critical regions of RC structures, as dictated in design codes such as the Eurrocode 8 for seismic-resistant design [17] in order to avoid brittle failure modes.…”
Section: Introductionmentioning
confidence: 99%